Day 2 Fri, November 08, 2019 2019
DOI: 10.2118/197083-ms
|View full text |Cite
|
Sign up to set email alerts
|

An Analytical Method for Optimizing Fracture Spacing in Shale Oil Reservoirs

Abstract: Hydraulic fracturing is the most prominent technique for increasing well productivity in shale oil and gas reservoirs. Spacing between perforation clusters, with Plug-and-Perf (PnP) fracturing method also believed to be spacing of fractures, is one of the parameters that need to be optimized in fracturing design. This work presents an analytical method to optimize fracture spacing based on the assessment of production data from multi-fractured horizontal wells. Five hydraulically fractured horizontal wells com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…), and production dynamic parameters (cumulative oil production and water cut). Using these parameters, Pearson's correlation coefficient can be calculated, and the higher the correlation coefficient, the greater the potential of refracturing [24][25][26][27][28].…”
Section: Well and Layer Selection Methodsmentioning
confidence: 99%
“…), and production dynamic parameters (cumulative oil production and water cut). Using these parameters, Pearson's correlation coefficient can be calculated, and the higher the correlation coefficient, the greater the potential of refracturing [24][25][26][27][28].…”
Section: Well and Layer Selection Methodsmentioning
confidence: 99%
“…To address overfitting, we adopted a strategy of simplifying the model structure when it was observed. For instance, if the ANN with three hidden layers (10, 10, 10) was found to be overfitting, we tested configurations with fewer nodes, such as (8,8,8), or even reduced the number of hidden layers, e.g., (10,10). We found that in pure ANN, an optimal configuration consisted of two layers with 7 and 2 nodes, yielding relatively good results for both wells.…”
Section: Support Vector Machines-artificial Neural Network (Svm-ann)mentioning
confidence: 99%
“…Fracture porosity directly controls the transportation and storage of hydrocarbons in these reservoirs. Additionally, the fracture properties affect the flow direction and permeability of the reservoir rocks [8]. Cores extracted during drilling, and less often, side wall cores, can be used to calculate fracture porosity [9,10].…”
Section: Introductionmentioning
confidence: 99%